National Educational Policies in India - Madhavedi, Sudhakar; P. Sudhaker; Ch. Prathima; G. Anusha (International Journal of Psychosocial Rehabilitation, 2019)
Education system in India has seen variegated changes right from Gurukula system till date. Monastic orders of education under the supervision of a guru were a favored form of education for the nobility in ancient India. The National Policy on Education (NPE) is a policy formulated by the Government of India to promote and regulate education in India. The policy covers elementary education to higher education in both rural and urban India. Essentially there are three education policies introduced in India since independence, by Prime Minister Indira Gandhi in 1968, by Prime Minister Rajiv Gandhi in 1986 and by Prime Minister Narendra Modi in 2020. The present paper talks about the National Education Policy 2020 from the perspective of the policies made in the country till date. The paper also attempts to bring out the Salient Features of National Policy on Education 2020.